History of the clay‐rich unit at Mawrth Vallis, Mars: High‐resolution mapping of a candidate landing site. Issue 11 (21st November 2015) - Loizeau, D.; Mangold, N.; Poulet, F.; Bibring, J.‐P.; Bishop, J. L.; Michalski, J.; Quantin, C.
Abstract: The Mawrth Vallis region is covered by some of the largest phyllosilicate‐rich outcrops on Mars, making it a unique window into the past history of Mars in terms of water alteration, potential habitability, and the search for past life. A landing ellipse had been proposed for the Curiosity rover. This area has been extensively observed by the High Resolution Imaging Science Experiment and the Compact Reconnaissance Imaging Spectrometer for Mars, offering the possibility to produce geologic, structural, and topographic maps at very high resolution. These observations provide an unprecedented detailed context of the rocks at Mawrth Vallis, in terms of deposition, alteration, erosion, and mechanical constraints. Our analyses demonstrate the presence of a variety of alteration environments on the surface and readily accessible to a rover, the presence of flowing water at the surface postdating the formation of the clay‐rich units, and evidence for probable circulation of fluids in the rocks at different depths. These rocks undergo continuous erosion, creating fresh outcrops where potential biomarkers may have been preserved. The diversity of aqueous environments over geological time coupled to excellent preservation properties make the area a very strong candidate for future robotic investigation on Mars, like the NASA Mars 2020 mission. Key Points: High‐resolution data enable high‐precision geological mapping at Mawrth Vallis Mapping shows the variety of depositional and alteration environments Highlights the interest of Mawrth Vallis as a future landing site